Noncognitive skills at the time of COVID-19: An experiment with professional traders and students - Marco Angrisani; Marco Cipriani; Antonio Guarino; Ryan Kendall; Julen Ortiz de Zarate Pina (Federal Reserve Bank of New York, 2023)
We study the stability of noncognitive skills by comparing experimental results gathered before and during the COVID-19 pandemic. Using a sample of professional traders, we find a significant decrease in agreeableness and locus of control and a moderate decrease in grit. These patterns are primarily driven by those with more negative experiences of the pandemic. Other skills, such as trust, conscientiousness, and self-monitoring, are unchanged. We contrast these results with those from a sample of undergraduate students whose noncognitive skills remain constant (except conscientiousness). Our findings provide evidence against the stability of noncognitive skills, particularly among professional traders.
Keywords: G40; D91; C93; 330; noncognitive skills; COVID-19; professional traders